Identification and quantification of Chimerism in bone marrow transplants leukemic patients - Sabbah, Majeed A. (Iraqi Journal of Cancer and Medical Genetics, 2017)
Quantification of chimerism after bone marrow transplantation is essential for evaluation the successful of engraftment after allogenic stem cells transplantation. The aim of this work is to use STR typing test for identification and quantification the chimerism in bone marrow transplant patients. Two patients subjected to bone marrow transplantation were analyzed. DNA extracted from patients (recipient) blood, cheek swabs and donor cheek swabs. Quantifiler Real time PCR kit was used for DNA quantification. Powerplex21 kit was used for amplification STR loci. STR profiling was performed by Genetic analyzer. DNA extraction and quantification were successfully performed with suitable quantity and purity. STR loci fully amplified and analyzed. In both cases recipient and Donor shared alleles with no DNA mixtures. Few loci showed Type 3 chimerism. In conclusion the results showed that the test successfully identify used for identification and quantification of chimerism in recipient patients. List of abbreviation: DNA= Deoxyribonucleic acid, STR- short tandem repeat, SCT= stem cells transplantation.